An arginase1- and PD-L1-derived peptide-based vaccine for myeloproliferative neoplasms: A first-in-man clinical trial - Grauslund, Jacob Handlos; Holmström, Morten Orebo; Martinenaite, Evelina; Lisle, Thomas Landkildehus; Glöckner, Hannah Jorinde; El Fassi, Daniel; Klausen, Uffe; Mortensen, Rasmus E. J.; Jørgensen, Nicolai; Kjær, Lasse; Skov, Vibe; Svane, Inge Marie; et al. (Frontiers in Immunology, 2023)
Introduction Arginase-1 (ARG1) and Programed death ligand-1 (PD-L1) play a vital role in immunosuppression in myeloproliferative neoplasms (MPNs) and directly inhibit T-cell activation and proliferation. We previously identified spontaneous T-cell responses towards PD-L1 and ARG1 derived peptide epitopes in patients with MPNs. In the present First-in-Man study we tested dual vaccinations of ARG1- derived and PD-L1-derived peptides, combined with Montanide ISA-51 as adjuvant, in patients with Janus Kinase 2 (JAK2) V617F-mutated MPN. Methods Safety and efficacy of vaccination with ARG1- derived and PD-L1-derived peptides with montanide as an adjuvant was tested in 9 patients with MPN The primary end point was safety and toxicity evaluation. The secondary end point was assessment of the immune response to the vaccination epitope (www.clinicaltrials.gov identifier NCT04051307). Results The study included 9 patients with JAK2-mutant MPN of which 8 received all 24 planned vaccines within a 9-month treatment period. Patients reported only grade 1 and 2 vaccine related adverse events. No alterations in peripheral blood counts were identified, and serial measurements of the JAK2V617F allelic burden showed that none of the patients achieved a molecular response during the treatment period. The vaccines induced strong immune responses against both ARG1 and PD-L1- derived epitopes in the peripheral blood of all patients, and vaccine-specific skin-infiltrating lymphocytes from 5/6 patients could be expanded in vitro after a delayed-type hypersensitivity test. In two patients we also detected both ARG1- and PD-L1-specific T cells in bone marrow samples at the end of trial. Intracellular cytokine staining revealed IFNγ and TNFγ producing CD4+- and CD8+- T cells specific against both vaccine epitopes. Throughout the study, the peripheral CD8/CD4 ratio increased significantly, and the CD8+ TEMRA subpopulation was enlarged. We also identified a significant decrease in PD-L1 mRNA expression in CD14+ myeloid cells in the peripheral blood in all treated patients and a decrease in ARG1 mRNA expression in bone marrow of 6 out of 7 evaluated patients. Conclusion Overall, the ARG1- and PD-L1-derived vaccines were safe and tolerable and induced strong T-cell responses in all patients. These results warrant further studies of the vaccine in other settings or in combination with additional immune-activating treatments.